PENGEMBANGAN ASSESSMENT BERBASIS VIDEO PADA KOMPETENSI DASAR MENGANALISIS SIMPANAN DANA DEPOSITO DI SMK NEGERI 1 TEMPEL KELAS X TAHUN AJARAN 2019/2020 - Priharsanti, Rosita Nur Wahyuningtyas; Prijowuntato, Sebastianus Widanarto (Universitas Sanata Dharma, 2021)
This research aims to create and develop a video-based assessment product in Basic Banking Course to teach the basic competence number 3.9, i.e. Time Deposits, to the tenth grade Accounting students and to determine the feasibility of the learning products based on media experts, assessment experts, linguists, accounting learning practitioners, and students’ responses. This research is a research and development (RD) consisting of 8 stages, namely : 1) research and information collection, 2) planning, 3) developing preliminary from of product 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) final product revision, 8) dissemination and implementation. The media were validated by a media expert, an assessment expert, a linguist, and an accounting teacher in SMK Negeri 1 Tempel. The media was tested on 47 tenth grade Accounting students of SMK Negeri 1 Tempel. The results showed that the level of feasibility of the video-based assessment product was categorized 1) as “feasible” based on the validation of assessment experts, with a mean score of 3.72; 2) as “strongly feasible” based on the validation of media experts, with a mean score of 4.17 ; 3) as “strongly feasible” based on the validation of linguists, with a mean score of 4.26; 4) and as “strongly feasible” based on the validation of accounting learning practitioners, with a mean score of 4.8. Student showed a positive response to this assessment product after being tested as shown in the observation sheet. Thus, the video-based learning product is feasible to be used in Accounting learning, especially Basic Banking Course discussing Basic Competence number 3.9: Time Deposits.